Role of Guduchi in musculoskeletal disorders: review based on Ayurvedic literature.: Array - , Dr. Ragini kumari (Ayurline: International Journal of Research in Indian Medicine, 2020)
Over the centuries, medicinal plants have served as a major source of medicine for prevention and treatment of diseases including musculoskeletal disorders. These medicinal plants are getting more importance around the globe and many studies provided safety and efficacy of such medicinal drug in different conditions. Guduchi is reported very effective in musculoskeletal disorders. Ayurveda has used Guduchi in many forms or with many combinations of drugs to treat disorders of musculoskeletal. Researchers reported Guduchi as anti inflammatory, antiarthritic, anti-immunomodulator, antioxidant[1]. It relief the symptom of pain, weakness, deformity, dystrophy, etc due to its properties. Hence we are going to review the role of Guduchi in MSK.